Characteristics of rambutan (Nephelium lappaceum L.) seed fat fractions and their potential application as cocoa butter improver - Azzatul F.; Jahurul Haque Akanda; Norliza J.; Norazlina M. R.; Hasmadi Mamat; Sharifudin Md Shaarani; Patricia Matanjun; Lee, Jau Shya (Rynnye Lyan Resources, 2020)
The utilization of rambutan seed (Nephelium Lappaceum L.) to produce fat (RSF) and its fractionation could be one of the solutions for better waste management and for ensuring its sustainable utilization. In this study, RSF was fractionated by two-stage acetone fractionation and their physicochemical properties such as fatty acid compositions, iodine value (IV), free fatty acid (FFA), slip melting point (SMP), and solid fat content (SFC) were investigated. The solid fraction-III (F2-S) exhibited the highest SMP (49.03°C) and lowest IV (27.57 g I2/100 g). The major fatty acids in all solid fractions were stearic (15.1- 21.6%), oleic (25.0-35.5%), and arachidic (42.7-46.9%) acids. The SFC of F2-S at 20°C (78.57%) and 35°C (22.95%) were found to be higher than solid fraction-I (F1-S), indicating a harder solid fraction. This study revealed that by performing fractionation of RSF, a cocoa butter improvers (CBI) could be prepared by blending them with other fats that have the potential to be utilized in chocolate manufacturing in tropical countries.